Development and application of dot-enzyme- linked immunosorbent (dot-ELISA) assay for detection of Brucella melitensis and evaluation of the shedding pattern in infected goats - Onilude, Opeyemi Mayowa; Mohd Yusoff, Md Sabri; Emikpe, Benjamin Obukowho; Tanko, Polycarp; Salisi, Mohd Shahrom; Mohammed Effendy (Taylor & Francis, 2017)
Early and accurate diagnosis of Brucella melitensis is essential for the treatment and control of brucellosis both in animals and humans. The thrust for the development of a rapid diagnostic technique to overcome the limitations of conventional microbiological and serological tests brought about this investigation on the development and application of dot-ELISA for antigen and antibody detection in infected goats. Fifteen apparently healthy Boer aged 2–3 years which tested negative for brucellosis using PCR and ELISA, were grouped into A (10 goats infected intraocularly with 107 CFU of B. melitensis) and B (5 goats) as control. Discharges (ocular, nasal, and vaginal) and blood were collected at days 3, 7, 10, 14, weekly until 42 post-infection (pi) for dot-ELISA, PCR, and RBPT. Dot-ELISA detected B. melitensis antigen and antibody in group A at day 3 and 7 pi, respectively with adequate sensitivity and specificity relative to PCR and RBPT. The bacteria shedding detected from discharges at day 3 pi in the nasal and ocular route with dot-ELISA. Group B were consistently negative. Values such as speed, simplicity, field adaptability, high sensitivity, and specificity make dot-ELISA a rapid and adequate technique for diagnosis of brucellosis in B. melitensis infected goats within few hours.